High Voltage Temperature Humidity Bias Test (THB) customized system and methodologies for reliability assessment of power semiconductor devices. (September 2019) - Cimmino, D.; Busca, R.; Ferrero, S.; Pirri, F.; Richieri, G.; Carta, R.
Abstract: High Voltage Temperature Humidity Bias Test (THB-HV) is currently the state of the art test method for reliability evaluation of power devices in high humidity environments at high voltage. These conditions have become especially significant in the case of power modules for the automotive industry and other applications in harsh environments. In this research work, a custom system for active monitoring of THB-HV testing is developed and customized, in order to evaluate different testing methodologies, intercept device degradation in real time, and allow for a controlled and more accurate failure analysis of the DUTs.